Metody odporne SAW w estymacji ryzyka portfela aktywów długoterminowych na przykładzie polskiego rynku funduszy inwestycyjnych - Orwat, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper aims at implementing selected robust estimation methods to multivariate outliers to determine examples of minimum-risk long-term assets portfolios. Examples of theoretical portfolios have been determined based on the actual data. The structure of those portfolios in terms of assets type was determined based on the structure of selected types of Polish open-end investment funds. Characteristics of portfolios determined based on classical maximum likelihood (ML) estimators of location and covariance matrix and based on robust minimum volume ellipsoid (MVE) and minimum covariance determinant (MCD) estimators have been compared. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 288-297